2021
DOI: 10.1142/s0217732321500358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of LHC Higgs couplings measurements on bosonic decays of the neutral Higgs sector in the scNMSSM

Abstract: We analyze the Next-to-minimal supersymmetric Standard Model with Grand unification boundary conditions under current theoretical and experimental constraints. We compute the mass spectrum of the model and focus on the three lightest particles in the Higgs sector (two CP-even scalars, [Formula: see text], [Formula: see text] and one CP-odd, [Formula: see text]). The reduced couplings of such particles, singlet-doublet components, their branching ratios to bosons and reduced cross-section to photons and massive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In a previous study, we showed the effect of the recent constraints on the properties of the neutral Higgs bosons, such as the mass spectrum, the singlet and doublets components, the reduced couplings of such particles, and their decays and reduced cross-section to bosons [37]. This paper will show the rest of the results of the possible decays of these particles and the reduced cross-section of them to fermions.…”
Section: Scan Strategymentioning
confidence: 75%
See 1 more Smart Citation
“…In a previous study, we showed the effect of the recent constraints on the properties of the neutral Higgs bosons, such as the mass spectrum, the singlet and doublets components, the reduced couplings of such particles, and their decays and reduced cross-section to bosons [37]. This paper will show the rest of the results of the possible decays of these particles and the reduced cross-section of them to fermions.…”
Section: Scan Strategymentioning
confidence: 75%
“…Based on this observation, the constraints of the recent LHC Higgs data on the lightest neutral Higgs states' properties are discussed in this paper. This method was used in a previous paper to investigate the effect of the latest LHC constraints on bosonic decays of possible lightest neutral Higgs bosons in the semi-constrained NMSSM (scNMSSM) with Grand unification boundary conditions [37] and will be shortly described in Section "Scan strategy". In this paper, we will apply this method to predict the effect of the recent constraints of the LHC on fermionic decays of neutral Higgs particles in scNMSSM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Higgs sector of both papers is associated with h 2 being the SM-like Higgs boson, which is different from the parameter space to be considered in this paper in which h 1 is the SM-like. The Higgs sector of this case has been recently analyzed in [59], where only the upper limit on DM is considered.…”
Section: Introductionmentioning
confidence: 99%